The Self Purification Through Dhikr in the Perspective of Imam Al-Ghazali - Maula Sari; Marhaban Marhaban (University of Darussalam Gontor, Indonesia, 2023)
Happiness is the goal of human life throughout the world. All teachings in religion are meant to bring about a happy life. However, mental disorders have now reached 13% associated with suicide with 800,000 suicide deaths worldwide. The human soul has an important role in the success of a person to achieve his goals. According to Imam Al-Ghazali, a person will gain success in his life with a healthy and calm soul, and purify himself through remembrance of Allah SWT. This research uses descriptive and analytical methods. The aims of self-purification are (1). Taṭahhur, which is an effort to cleanse the soul of all the bad things that have been done in the past. (2). Takhallaq is an effort to adorn oneself with praiseworthy morals. While (3). Taḥaqquq is an effort to realise noble positions. The virtues of dhikr according to Imaam Al-Ghazali by doing one of them. Can get forgiveness, anticipate forgetfulness and negligence and reassure the soul. By doing dhikr through self purification, it is a means to get closer to Allah and have a sense of attachment to Allah SWT.